Body roundness index, frailty, and stroke - Laura Bee Gek Tay (Annals of the Academy of Medicine, Singapore, 2026)
Stroke remains a leading global cause of death and disability. Primary prevention efforts to reduce the burden of stroke should focus on the management of modifiable risk factors, and 10 such factors were noted to account for approximately 90% of the population-attributable risk of stroke in the INTERSTROKE study.1 These risk factors are often inter-related, with obesity contributing to major cardiovascular risk factors including hypertension, diabetes mellitus, and dyslipidaemia. A meta-analysis of prospective cohorts found that metabolically unhealthy phenotypes carry roughly double the stroke risk at any body weight, whereas metabolically healthy obesity confers only a modest excess (risk ratio of 1.17), suggesting that much of obesity-related stroke risk is transmitted through metabolic intermediaries, with a smaller direct contribution.2 In INTERSTROKE, abdominal obesity defined by waist-to-hip ratio, rather than body mass index (BMI), carried an independent population-attributable risk of 18.6%,1 and central adiposity has been linked to greater stroke severity and poorer early functional outcome in a single-centre prospective cohort,3 which may partly explain the obesity paradox previously described for BMI. This has been attributed to the detrimental effects of visceral fat accumulation in driving systemic inflammation, insulin resistance, and cardiovascular risk. The body roundness index (BRI) was introduced by Thomas et al. in 2013 to quantify abdominal adiposity and overall body fat by integrating the geometric relationship between waist circumference and height, with subsequent research validating its relationship with visceral adiposity and metabolic syndrome.4,5